The function of the thaler in determining the exchange rates of European currencies in the second half of the 16th century - Vorel, Petr (My University, 2022)
The author summarizes the origin and development of the thaler since its emergence in Central Europe in the 1520s to the general spread of the term “thaler” for large silver coins in the 1540s as well as the attempts to replace the thaler with another type of coin in the Roman-German Empire under the Second and Third Imperial Coin Order. The year 1566 was a major turning point. The “imperial thaler” was redefined in metrological terms and the collection of custom duties in the North Sea straits was regulated, which (instead of gold coins) continued to be collected in silver thalers. This move spurred the expansion of the thaler coins in those countries of continental Europe that used the North Sea trade route. At that time, the thaler also became the equivalent for mutual conversions of the most important monetary systems. This is evidenced by the exchange rates from the end of the 16th century from Hamburg. In them, the ”imperial thaler” serves as a tool for the mutual conversion the seven major currencies used in the North Sea and Baltic trade areas (the Lübeck mark, the Hamburg pound, the Antwerp pound, the Amsterdam pound, the imperial Rhine gulden, the Lisbon milreis and the Polish gulden)
Funkce tolaru při určování směnných kurzů evropských měn ve 2. polovině 16. století
Keywords: coin; thaler; currency; 16th century; Europe; mince; taler; měna; 16. století; Evropa